Referencing an editorial ontology from the TEI: an attempt to overcome informal typologies - Šimek, Jakub (2019)
The introduction of TEI P5 in 2007 was accompanied by efforts of mapping contents of TEI documents to high level conceptual models like CIDOC CRM. They focused on prosopographical information connecting the textual content with index metadata. Moreover, a flexible use of the <taxonomy> element was implemented, allowing for ontology-like thesauri which can be referred to by pointers from an edition. While these mechanisms for named entities and terms enable powerful indexing, little attention so far has been given to formalizing the ways of dealing with editorial and documentary typologies which are used in attributes like e.g. type, @function and @reason. These typologies refer to document types, textual and editorial phenomena, the processes of text production and text redaction and similar categories of concepts which characterize the text itself rather than external entities referred to by the textual content. Attributes like @type do not permit the use of pointers to formal conceptual definitions as their expected data type is teidata.enumerated, not URI pointers (although the <equiv> element in ODD specifications could map different XML components to formal URIs externally). This paper presents the attempt made at the Heidelberg University Library to enable in TEI documents pointers to definitions of editorial phenomena administrated in a OWL ontology (“heiEDITIONS Concepts”) in order to replace teidata.enumerated attributes with URI pointer mechanisms. This strategy makes use of a few TEI attributes like @ana whose data type is teidata.pointer and some additional pointer attributes provided by a schema extension. A “private URI scheme” stated in the TEI header allows the use of abbreviated URI forms. The goal of this institutional strategy is not only a standardization of the TEI encoding adopted by in-house edition projects and cooperative endeavours but also a transparency in documentary and editorial terminology used in TEI code.